TEACHERS' LEADERSHIP STYLE AND STUDENTS' LEARNING MOTIVATION IN JUNIOR HIGH SCHOOLS - Wagiyo, Supiah; Nawanto, Condro (Magister Program Studi Pendidikan Ekonomi, 2026)
Teachers' leadership style is a critical determinant of instructional effectiveness, particularly in English as a Foreign Language (EFL) contexts where student engagement is essential. This study aims to identify the dominant leadership styles applied by English teachers and to evaluate the level and characteristics of students' learning motivation in junior high schools on Bangka Island. Employing a quantitative survey design, data were collected from 20 English teachers and 20 seventh-grade students. The Leader Behavior Description Questionnaire (LBDQ) and a multi-dimensional motivation scale were utilized. Data analysis involved descriptive statistics and mapping into the Ohio State leadership quadrants. Findings reveal that teachers predominantly exhibit a